Renal outcomes with sodium glucose cotransporter 2 (SGLT2) inhibitor, dapagliflozin, in obese insulin-resistant model - Krit Jaikumkao (2018)
© 2018 Elsevier B.V. A growing body of evidence indicates that obesity and insulin resistance contribute to the progression of renal disease. This study was performed to determine the effects of dapagliflozin, a novel sodium glucose cotransporter 2 (SGLT2) inhibitor, on renal and renal organic anion transporter 3 (Oat3) functions in high-fat diet fed rats, a model of obese insulin-resistance. Twenty-four male Wistar rats were divided into two groups, and received either a normal diet (ND) (n = 6) or a high-fat diet (HFD) (n = 18) for 16 weeks. At week 17, the HFD-fed rats were subdivided into three subgroups (n = 6/subgroup) and received either a vehicle (HFD), dapagliflozin (HFDAP; 1.0 mg/kg/day) or metformin (HFMET; 30 mg/kg/day), by oral gavage for four weeks. Metabolic parameters, renal function, renal Oat3 function, renal oxidative stress, and renal morphology were determined. The results showed that obese insulin-resistant rats induced by HFD feeding had impaired renal function and renal Oat3 function together with increased renal oxidative injury. Dapagliflozin or metformin treatment decreased insulin resistance, hypercholesterolemia, creatinine clearance and renal oxidative stress leading to improved renal function. However, dapagliflozin treatment decreased blood pressure, serum creatinine, urinary microalbumin and increased glucose excretions, and showed a greater ability to ameliorate impaired renal insulin signaling and glomerular barrier damage than metformin. These data suggest that dapagliflozin had greater efficacy than metformin for attenuating renal dysfunction and improving renal Oat3 function, at least in part by reducing renal oxidative stress and modulating renal insulin signaling pathways, and hence ameliorating renal injury.